Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1021/cg501314m
|View full text |Cite
|
Sign up to set email alerts
|

Trapping of Octameric Water Cluster by the Neutral Unclosed Cryptand Environment

Abstract: Unclosed cryptands (UCs) are neutral and easily accessible compounds with precisely defined spatial arrangement of various functional groups. They readily form crystals with a unusually high packing efficiency (≥0.8), thus providing a well-suited 3Dframework for study of supramolecular assemblies. Herein, one example of the discrete eight-membered water cluster trapped in the matrix of UC 1 is presented. X-ray, ATR FT-IR, and DFT studies indicate extraordinary stability of this assembly, which originated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…The host 2 has been synthetized and its crystal structure was determined by X-ray crystallography. It was found, unexpectedly, that host 2 contains near the same octameric water cluster as previously found in the crystal structures of analogs 1a [ 33 ] and 1b [ 10 ] . A comparative crystal structure analysis has been carried out to identify the role of macrocyclic skeleton and lariat arm on the formation of water clusters in the crystal lattice of hosts 1a – b and 2 .…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…The host 2 has been synthetized and its crystal structure was determined by X-ray crystallography. It was found, unexpectedly, that host 2 contains near the same octameric water cluster as previously found in the crystal structures of analogs 1a [ 33 ] and 1b [ 10 ] . A comparative crystal structure analysis has been carried out to identify the role of macrocyclic skeleton and lariat arm on the formation of water clusters in the crystal lattice of hosts 1a – b and 2 .…”
Section: Introductionsupporting
confidence: 70%
“…Due to their inherent flexibility, they are able to adjust their shape to highly demanding guests, in particular anions. Lately, we showed that 26-membered pentamide unclosed cryptands are able to accommodate octameric water clusters in their structure [ 10 , 33 ], proving that such molecules are a good choice for studying the hydration phenomena of small organic compounds, as well as serving as a model for more complicated structures of biological importance. It may prove very useful as studying the hydration behavior of biological molecules still presents a challenge for modern science [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unclosed cryptands Uc1-Uc5 [30][31][32] are structurally related to previously mentioned macrocycles M1-M13, however, only one side contains meso diacid moiety (dipicolinic acid), while the other side is constructed here from diacid derived from 2,6-dihydroxyaniline. The nitrogen atom of the latter group is a part of amide equipped with an additional p-nitrophenyl substituent (lariat arm) which is introduced at the intraannular position of the macroring.…”
Section: Unclosed Cryptands (Group Iii)mentioning
confidence: 99%
“…8). Firstly, although macrocyclic scaffold is quite well preorganized for the binding of various guests via H-bond interactions, 31,32,45,46 complexation of a guest which is solely an H-bond acceptor (such as chloride), requires a 180°degree rotation of the lariat arm accompanied with the breaking of the intramolecular H-bond. This in turn, enables very strong, albeit not highly directional interaction with an anion (d N⋯Cl − = 3.12 Å, ≤159°), which has no direct contact with the TBA + counterion (Fig.…”
Section: Unclosed Cryptands (Group Iii)mentioning
confidence: 99%
“…For the importance in both chemical and biological processes, the water–water interaction in water aggregates of varying degree has been the subject of both experimental and theoretical research in the past few decades. 1 15 These efforts have been primarily targeted to elucidate the structure–property correlations in such systems. In the biological systems, water maintains the stability and proper functioning of enzymes and proteins.…”
Section: Introductionmentioning
confidence: 99%